Dog's Day Out - The Star (2008)
The annual carnival for dog lovers and owners is back with plenty of games in store. The event is aimed at promoting responsible pet ownership, and funds collected will be channelled to Pro-Kasih, a catch-neuter-release project which helps control the population of stray cats.